Justification and Excuse, Law and Morality - Callbo, Simon (2003)
Anglo-American theorists of the criminal law have concentrated on-one is tempted to say obsessed over -the distinction between justification and excuse for a good quarter-century and the scholarly attention has purchased unusually widespread agreement. Justification defenses are said to apply when the actor's conduct was not morally wrongful; excuse defenses lie when the actor did engage in wrongful conduct but is not morally blameworthy. A near-consensus thus achieved, theorists have turned to subordinate matters, joining issue most notably on the question of whether justifications are subjective -turning upon the actor's reasons for acting-or objective -involving only facts independent of the actor's beliefs and motives. This Article seeks to demonstrate that the prevailing understanding is wrong. Drawing on the well-known distinction between conduct rules and decision rules, it argues that the distinction between justification and excuse, for purposes of a criminal law taxonomy, is only this: A justified action is not criminal, whereas an excused defendant has committed a criminal act but is not punishable. To readers only marginally acquainted with the relevant literature, this claim may seem far from extravagant, for occasional statements to the same effect can be found in the case law and commentary. In fact, however, theorists have not appreciated just how this articulation of the distinction differs from the orthodox one, nor what consequences follow. This Article attempts to remedy that defect. One lesson of a systematic investigation into these competing formulations is that the long-running debate over whether justifications, properly understood, are subjective or objective is misconceived. This is a debate over policy broadly conceived, not (as it so often purports to be) a matter of conceptual analysis. More generally, this Article's examination of justification and excuse constitutes a case study in the complex relationship between legal and moral reasoning, and highlights the importance of distinguishing arguments that advance substantive value judgments from those that purport to analyze our conceptual apparatus. It may be that conceptual analysis is no less contestable or value-laden than is substantive normative argument (though perhaps it is). In any event, they are not the very same enterprise and a first step to clear thinking-in the criminal law and elsewhere-is to keep them distinct